LIVELIHOOD DIVERSIFICATION AMONG RURAL HOUSEHOLDS IN SOUTHWESTERN NIGERIA (2014)
Diversification is a necessity in rural areas, where farming alone rarely provides sufficient means of survival. Conceptualisation of livelihood diversification as plurality of activities from past studies is too narrow. Rather, livelihood diversification should be conceived in terms of the interplay of ability, assets and activities. Therefore, livelihood diversification among rural households in southwestern Nigeria was investigated. Multistage random sampling technique was used to select the respondents for the study. Ekiti, Ogun and Osun states were selected from the six states of southwestern Nigeria. Twenty percent of rural LGAs were selected in the respective states to give 9, 11, and 16 LGAs. Ten percent of wards in each LGA was selected, from which 2.5% of households were selected to give 405 respondents. Structured interview schedule was used to collect data on respondents‟ socio-economic characteristics, livelihood abilities, livelihood activities, reasons for diversification, sources of information, livelihood assets, season of diversification, constraints and level of diversification. Indices of livelihood abilities, activities, assets, constraints and level of diversification were developed for categorisation of respondents. Data were analyzed using frequency counts, percentage, means, Pearson‟s Product Moment Correlation, ANOVA, linear and binomial regression at p = 0.05. Respondents‟ age, household size and income were 52.3±10.9 years, 4.82±1.88 and N18851.85±16593.65 respectively. Most (96.3%) of the respondents were males, married (87.9%) and Christians (63.0%). Majority had farming as primary occupation (57.34%), no formal education (62.2%) and acquired their land through inheritance (73%). Most (72.4%) of them diversified into arable crop farming while 57.0% into off-farm activities. Majority (72.4%) diversified for sales and consumption only while 76.3% diversified in both seasons. Sources of UNIVERSITY OF IBADAN LIBRARY 3 information on livelihood diversification included radio (89.9%) and relatives/friends (58.5%). Rural households had low livelihood assets ( x =37.39±11.67) and activities ( x =3.15±1.27), while they had high livelihood abilities ( x =63.27±12.53). Constraints to livelihood diversification were lack of infrastructural facilities (91.9%), inadequate livelihood assets (82.0%) and poor transportation system (66.9%). Respondents‟ level of livelihood diversification was significantly increased by primary occupation (β=0.64), income from farming (β = 0.16), length of stay (β = 0.28) and income from non-farm activities (β = 0.13). Significant relationship existed between constraints (r=-0.130) and level of livelihood diversification. However, frequency of visits to urban centres (β = -0.25) significantly reduced respondents‟ level of livelihood diversification. Livelihood assets (F = 35.095), activities (F = 2.891) and level of livelihood diversification (F = 6.075) were also significantly different across the states. Livelihood diversification was significantly influenced by livelihood ability (β = 0.860), assets (β = 0.29) and activities (β = 0.09) among rural households across the states. Level of livelihood diversification of rural households was low, in spite of their high level of livelihood abilities. Differences in level of livelihood assets and activities accounted for non-uniform level of livelihood diversification across the states. Therefore, enhanced livelihood assets and uniformity in rural development initiative could improve livelihood diversification of rural households in southwestern Nigeria. Keywords: Rural asset, Livelihood ability, Plurality of activities. Word counts: 491